Translation of John Steinbeck’s Grapes of Wrath in Soviet Lithuania. Whose Wrath in the Title? - Valentinavičienė, Daina (Vertimo studijos, 2025)
This paper is part of a series of articles on the censorship of religious motives in Soviet-era Lithuanian translations. It deals with the 1947 Lithuanian translation of John Steinbeck’s The Grapes of Wrath by Karolis Vairas-Račkauskas, in particular focussing on the translation of the novel’s title. The study makes use of two translation manuscripts, revealing the translator’s choices at different stages of translation. The title of the published translation diverged from the translator’s final choice and replicated the precedent Russian translation. Based on foreign literary criticism, the paper overviews J. Steinbeck’s use of Christian symbols and images in the novel and argues that the modification of the title in translation narrowed the meaning potential of the original, emphasizing the interpretation that suited Soviet ideology. The Soviet-era paratexts by Lithuanian and Russian critics are also discussed, attesting to the effort to shape the reception of the novel for Soviet readers in one particular direction.